2023
DOI: 10.3390/vision7010006
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Penguin Visual System

Abstract: Penguins require vision that is adequate for both subaerial and submarine environments under a wide range of illumination. Here we provide a structured overview of what is known about their visual system with an emphasis on how and how well they achieve these goals. Amphibious vision is facilitated by a relatively flat cornea, the power in air varying from 10.2 dioptres (D) to 41.3 D depending on the species, and there is good evidence for emmetropia both above and below water. All penguins are trichromats wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…Few studies have reported effects of UV radiation due to the ozone hole on Antarctic vertebrates, with most studies restricted to animals in zoos (located at low–mid‐latitudes and where animals are kept under artificial light sources, Bliss et al., 2015; Karentz & Bosch, 2001; Woodhouse et al., 2016). A recent review on penguin visual systems shows that UV light may be relevant for sexual behavior in some penguin species (Hadden & Zhang, 2023). These studies show that penguin species vary in the extent to which UV radiation penetrates their eyes, with king penguin lenses absorbing almost all radiation below 370 nm while in gentoos more light is transmitted into the eyes (Hadden et al., 2023).…”
Section: The Extended Ozone Hole and Loss Of Sea Ice: Impacts For Mar...mentioning
confidence: 99%
“…Few studies have reported effects of UV radiation due to the ozone hole on Antarctic vertebrates, with most studies restricted to animals in zoos (located at low–mid‐latitudes and where animals are kept under artificial light sources, Bliss et al., 2015; Karentz & Bosch, 2001; Woodhouse et al., 2016). A recent review on penguin visual systems shows that UV light may be relevant for sexual behavior in some penguin species (Hadden & Zhang, 2023). These studies show that penguin species vary in the extent to which UV radiation penetrates their eyes, with king penguin lenses absorbing almost all radiation below 370 nm while in gentoos more light is transmitted into the eyes (Hadden et al., 2023).…”
Section: The Extended Ozone Hole and Loss Of Sea Ice: Impacts For Mar...mentioning
confidence: 99%